Redescription of three cirolanid isopods (Crustacea: Peracarida) from Indonesia - Sidabalok, Conni M.; Bruce, Niel L. (Zootaxa, 2016)
Three species of Cirolanidae described by Nierstrasz in 1931 are redescribed from the type material: Cirolana indica Nierstrasz, 1931, with new material from Singapore and Lombok Island, Indonesia; C. vanhoeffeni Nierstrasz, 1931; and C. stebbingi Nierstrasz, 1931, which is here transferred to the genus Politolana Bruce, 1981 based on the elongate body, long peduncle of pleopod 1, narrow and slender frontal lamina, flat and robust carpus of pereopod 7, long and acute robust setae on merus–propodus pereopod 1, secondary unguis on dactylus, and antenna peduncle articles 1–2 shorter than the subequal articles 3–5.